2017
DOI: 10.1007/s13157-017-0933-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Oxygen Profiles and Denitrification Rates in Freshwater Sediments

Abstract: Vegetated ditches and wetlands are important sites for nutrient removal in agricultural catchments. About half of the influx of inorganic nitrogen can be removed from these ecosystems by denitrification. Previous studies have shown that denitrification in aquatic ecosystems is strongly temperature dependent, resulting from temperature-dependent oxygen availability. Here, we study short-term temperature effects on sediment oxygen demand (SOD) and the maximum depth of oxygen penetration into the sediment (Z), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…N 2 O is typically derived during nitrification of NH 4 -N under oxic conditions and from the coupled nitrification-denitrification reactions under suboxic conditions, which explains the increase in N 2 O coinciding with the NH 4 -N decrease. Both nitrification and denitrification are strongly temperature-dependent (Veraart et al 2011;de Klein et al 2017). Heatwave treatments in our experiment had higher N 2 O concentrations, coinciding with a drop in O 2 concentrations, which further indicates that freshwater N 2 O emissions can be strongly temperature dependent and can be boosted under climate change (Parton et al 2001;Veraart et al 2011).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…N 2 O is typically derived during nitrification of NH 4 -N under oxic conditions and from the coupled nitrification-denitrification reactions under suboxic conditions, which explains the increase in N 2 O coinciding with the NH 4 -N decrease. Both nitrification and denitrification are strongly temperature-dependent (Veraart et al 2011;de Klein et al 2017). Heatwave treatments in our experiment had higher N 2 O concentrations, coinciding with a drop in O 2 concentrations, which further indicates that freshwater N 2 O emissions can be strongly temperature dependent and can be boosted under climate change (Parton et al 2001;Veraart et al 2011).…”
Section: Discussionsupporting
confidence: 54%
“…Although studies on combined effects of nutrients and warming show strong interactive effects on GHG emission (Davidson et al 2015(Davidson et al , 2018Aben et al 2017), little is known about specific effects of heatwaves and restoration measures. Microbial processes like mineralization, nitrification and denitrification are all temperature dependent (Veraart et al 2011;de Klein et al 2017), while restoration measures may modulate these processes by reducing C, N and P availabilities needed for microbial activities (Redfield 1958). As a result, the nutrient cycling and GHG emission can be largely changed by the altered microbial processes due to restoration and climate change even without considering the role of primary producers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, both the nutrient levels (TP, TN) and temperature in eutrophic Lake South were significantly higher than those in oligotrophic Lake Basomtso. As we know, excessive nutrients and high temperature can induce the growth and reproduction of planktonic algae and significantly increase the biomass of phytoplankton [20,21,42]. This may be the reason why the density of phytoplankton in eutrophic South Lake was higher than that in oligotrophic Lake Basomtso.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the community dynamics of aquatic bacteria vary with biotic and abiotic environmental variables, e.g., temperature, availability of nutrients, predation, and interactions with other organisms, including phyto-and zooplankton [16][17][18]. Previous studies have showed that the main driving factors, including nitrogen, phosphorus, and temperature, could alter the taxonomical structure of the bacterial community in freshwater lakes [19][20][21]. However, these studies were mainly focused on the taxonomical composition of the sediment community [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In impermeable sediments like those in lowland, artificial irrigation canals, saturation may also affect OC mineralization by limiting O 2 penetration and the sediment volume where aerobic microbial activities take place. O 2 microprofiles revealed in fact that in organic sediments O 2 penetration depth is confined to the upper few millimeters (de Klein et al 2017). During water level drawdown, the enhanced O 2 penetration is expected to expand the volume of sediments with aerobic microbial activity, and enhance the efficiency of mineralization as a consequence of higher energy yield (Baldwin and Mitchell 2000;Foulquier et al 2013).…”
Section: Introductionmentioning
confidence: 99%